The Implementation of English Team Teaching at a Senior High School in Malang - Dina Puspita Rini; Utami Widiati; Sri Widayati (TEFLIN Journal: A publication on the teaching and learning of English, 2008)
This descriptive-qualitative case study was conducted to describe the implementation of English team teaching at SMA Negeri (Senior High School) 2 Malang in terms of the objectives, the shared responsibilities among teachers, perceptions of the teachers and students, and factors influencing the implementation. Four English teachers and 106 students of Year 10 and Year 11, selected using a purposive random sampling technique, were involved. The data were collected through interviews and questionnaire. The findings show that the reasons for implementing team teaching were the adequate number of English teachers, empowerment in the subject they taught, and forming bonds among teachers and students. Different types of shared re-sponsibilities were found among the teachers. Additionally, both the teachers and the students had positive perceptions concerning the effectiveness of team teaching. In-stead of having difficulties, all the teachers saw the existence of supporting factors in their implementing team teaching.